2022
DOI: 10.1002/joc.7609
|View full text |Cite
|
Sign up to set email alerts
|

Wet season rainfall onset and flash drought: The case of the northern Australian wet season

Abstract: In this paper, we report on the frequency of false onsets of wet season rainfall in the case of the Northern Australian wet season and investigate the role of largescale tropical climate processes such as the El Niño-Southern Oscillation, Indian Ocean Dipole (IOD) and Madden-Julian Oscillation. A false onset occurs when a wet season rainfall onset criterion is met, but follow-up rainfall is not received for weeks or months later. Our analysis of wet season rainfall data from 1950 through 2020 shows a false ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 86 publications
1
2
0
Order By: Relevance
“…Contrary to the previous common perception that flash droughts are rare events, they occur more frequently than the other two types. Some previous studies seem to provide similar evidence of frequent, rapid drops in soil moisture and high frequency of flash drought [12,16,33]; here, our results reinforce the conclusion that the rapid transition from an energy-limited to a water-limited condition is a prevalent phenomenon in most of the regions. Note that our definition of the flash drought was more restrictive than previous studies.…”
Section: The Prevalence Of Rapid Intensification Over the Globesupporting
confidence: 90%
See 1 more Smart Citation
“…Contrary to the previous common perception that flash droughts are rare events, they occur more frequently than the other two types. Some previous studies seem to provide similar evidence of frequent, rapid drops in soil moisture and high frequency of flash drought [12,16,33]; here, our results reinforce the conclusion that the rapid transition from an energy-limited to a water-limited condition is a prevalent phenomenon in most of the regions. Note that our definition of the flash drought was more restrictive than previous studies.…”
Section: The Prevalence Of Rapid Intensification Over the Globesupporting
confidence: 90%
“…However, in some hotspots, flash drought can occur twice or even three times a year, leading to a debate about whether it can be considered a drought if the criterion is met so frequently. One undeniable fact is that the frequent, rapid changes in soil moisture evidenced by the rapid transitions from an energy-limited environment to a water-limited environment are part of the climatology of the locations at least [33].…”
Section: Discussionmentioning
confidence: 99%
“…Projections show an exacerbation in the occurrence and severity of drought in the future in the Northern Territory, Australia [ 24 , 25 ]. For instance, Wang et al [ 26 ] found drought severity increased from 44.26 cm/month to 52.19 cm/month in 2006–2009 and 2018–2020, respectively, and predicted an increased severity due to changes in El Niño and the Indian Ocean Dipole.…”
Section: Introductionmentioning
confidence: 99%